Surface modification of Co3O4 nanostructures using wide range of natural compounds from rotten apple juice for the efficient oxygen evolution reaction. (12th May 2023) - Laghari, Abdul Jaleel; Aftab, Umair; Shah, Aqeel Ahmed; Solangi, Muhammad Yameen; Abro, Muhammad Ishaque; Al-Saeedi, Sameerah I.; Naeim, Noha; Nafady, Ayman; Vigolo, Brigitte; Emo, Melanie; Molina, Antonia Infantes; Tahira, Aneela; et al.
Abstract: In this study, a new strategy has been produced to use a rotten apple juice as a source for the surface modification of Co3 O4 nanostructures, giving rise to efficient electro-catalysts for driving oxygen evolution reaction (OER) at relatively low over potential. We have studied the morphology, chemical composition, and crystalline aspects of Co3 O4 nanostructures using different analytical techniques. The Co3 O4 nanostructures grown with rotten apple juice were observed with low impurity of Fe and P, surface modification, reduced particle size, high concentration of oxygen vacancies, defects and cubic phase of Co3 O4 . Furthermore, we have used the surface modified Co3 O4 nanostructures for water electrolysis and noticed the significant performance towards OER in alkaline conditions. The electrochemical characterization revealed that the Co3 O4 nanostructure prepared with 20 mL of rotten apple juice exhibits an overpotential value of 269 mV at 20 mA/cm 2 current density. The charge transport resistance (Rct) at the interface was estimated around 118.9 Ω, confirming an excellent reaction kinetics on the Co3 O4 nanostructures and highly supported efficient performance towards OER. The Co3 O4 nanostructures prepared with 20 mL of rotten apple juice has shown an acceptable durability for 40 h, verifying the long-term use. The performance of Co3 O4 nanostructures with apple juice could be attributed to high oxygen vacancies due to high density of Co 2+ ions on the surface, impurities of Fe and P, reduced nanoparticle size, defects in the structures, and favorable chemical composition. At the end, surface modified Co3 O4 nanostructures was observed as an outperformed electrocatalyst when prepared with rotten apple juice. Therefore, this can be used in diverse purposes including energy conversion and storage applications. Highlights: An innovative and green approach presented for the surface modification of Co3 O4 . Rotten apple juice significantly tuned the surface properties of Co3 O4 . Natural reducing agents have also enhanced electrocatalytic properties of Co3 O4 . Oxygen evolution reaction was performed at low energy demand of 269 mV. Co3 O4 prepared with rotten apple juice were found durable for 40 h.